The Effects of DEM Resolution in Extraction of Physiographic and Hydrological Characteristics of Karde-Dam Watershed - Samira, Alizadeh; Abdolhamid, Dehvari; Akbari, Abolghasem (2015)
This works evaluate the effect of DEM resolution on watershed delineation and particularization in Kardeh-Dam Watershed, Iran. A series of DEM at resolutions of 10, 20, 30, 40, 50 and 60 m resolution are investigated and compared with the reference DEN derived from the topographic map at scale of 1:25000.The HEC-GeoHMS is used as GIS tools for watershed delineation and particularization.